Directions for the Application of Analytical Procedures in Auditing - Hamzaevich, Choriyev Isroil (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The article highlights important areas of using analytical operations at the initial stage of audits for the effective organization of audit activities in our republic in a competitive economy and improving the quality of its work.